A new PWM scheme for cascaded multilevel inverter using multiple trapezoidal modulation signals - Ayob, S. M.; Salam, Z. (2004)
This work proposes a new PWM scheme for the cascaded multilevel inverter (CMI). The proposed scheme uses multiple trapezoid modulating signals with a single triangular carrier. The scheme offers several advantages compared to sinusoidal PWM (SPWM) in terms of easy and fast real-time waveform generation with higher fundamental output voltage. This paper details the technique and the parameters that affect its performance. A low power 5-level CMI prototype is constructed to verify the viability of the modulation scheme.